Characterization and optimization of an extractor-type catalytic membrane reactor for meta-xylene isomerization over Pt-HZSM-5 catalyst - Daramola, Michael Olawale (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Process Engineering))--University of Stellenbosch, 2010.